PENGARUH SER TERHADAP ROE DAN EPS EMITEN INDUSTRI KEUANGAN TAHUN 2013-2019 - Arifiandy, Dicky Ridho; Ekawaty, Marlina (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Indonesia is a country with the largest Muslim population in the world. This makes Indonesia have great potential in developing the Islamic financial sector. In fact, Indonesia hasn't been able to maximize its potential. One of the sharia investment that shows positive developments is Sukuk. This study aims to analyze the effect of Sukuk to Equity Ratio on Return on Equity and Earning Per Share of issuers on the Indonesia Stock Exchange in 2013-2019. This study uses regression analysis to panel data with quantitative method. The results of this study indicate that the Sukuk to Equity Ratio has a significant positive effect on Return on Equity and Earning Per Share. These results are in accordance with the hypothesis formulated in this study.